Cảm nhận hạnh phúc học đường của học sinh phổ thông: Sự khác biệt theo cấp học, địa bàn và các khuyến nghị cải thiện - Nguyen Hoang Bao, Ngoc; Sái Công Hồng, Sái Công Hồng (Tạp chí Giáo dục, 2026)
School happiness has increasingly emerged as a significant concern in contemporary education. This study aimed to examine differences in students’ perceived school happiness across educational levels and geographical areas, and to identify priority indicators for improvement to enhance students’ school happiness. A total of 7,564 students from three educational levels across five provinces/cities completed a 42-item questionnaire designed to assess general education students’ perceptions. The collected data were analyzed using descriptive statistics, analysis of variance (ANOVA), and the Priority Index for improvement. The findings indicated that the overall Happy School score reached 4.326 out of 5, suggesting a generally positive evaluation among students. In addition, statistically significant differences in the overall score were found by educational level and geographical area. Specifically, the score showed a decreasing trend from primary to upper secondary education, while students in rural areas reported higher school happiness than those in urban and mountainous areas. The priority areas for improvement reflected both common issues across the three educational levels and specific concerns associated with each level. Based on these findings, several recommendations are proposed to support schools in using assessment results as an evidence-based management tool for improving the quality of the school environment.